POLA HIDUP SEHAT LANSIA DI PANTI SOSIAL TRESNA WERDHA (PSTW) BUDI LUHUR JAMBI - Vevi Suryenti Putri; Fitriyani Fitriyani; M Ilham (Jurnal Abdimas Kesehatan (JAK), 2019)
Aging is a period of change experienced by individuals both physically and psychologically due to a decrease in bodily functions. Therefore an effort is needed to maintain the health status of the elderly at the highest level in order to avoid disease. In order to stay active until old age, since young people need to maintain a healthy lifestyle by consuming foods that are nutritionally balanced, doing physical activity / exercise properly and regularly and not smoking. The general condition of the elderly in Jambi noble PSTW is still reluctant to regulate their healthy lifestyle such as regulating diet, rest and exercise so that it is susceptible to diabetes mellitus or diabetes, heart disease, hypertension, cancer or malignancy. The target expected in this activity, namely: Elderly is expected to be able to understand how a healthy lifestyle, the elderly can be independent in regulating their healthy lifestyle, the elderly can maintain / improve their health status. The extension activities will be carried out with the stages of: Distributing leaflets to the audience, Pasting posters, Directing the audience to the room to be counseled, Conducting the opening to be delivered by the moderator, Delivering counseling material to be delivered by the presenter, Evaluating the audience, Documenting activities. The participants of the counseling attended were 27 elderly where the initial target of the group of 30 elderly was not fulfilled because some of the elderly were still treated at the clinic. Out of the whole extension program activities have been carried out smoothly and well, both in terms of conducive space, competent presenter material and elderly who are active in the counseling.